Development and evaluation of Chia seed-based nanofibers and nanoemulsions for Bacillus coagulans Encapsulation - Shirin Rashnoei; Mozhgan Shahamirian; Sedigheh Yazdanpanah; Elham Ansarifar (Scientific Reports)
Abstract This study explores the encapsulation efficiency of composite nanofibers and nanoemulsions derived from chia seed mucilage (Salvia hispanica L.), a natural hydrocolloid with notable bioactive properties. Nanofibers, known for their high surface area and stability, and nanoemulsions, recognized for their enhanced bioavailability, were utilized to encapsulate Bacillus coagulans. Chia mucilage demonstrated a DPPH radical scavenging activity of 67.88% at 350 µg/mL and moderate antimicrobial effects, with inhibition zones of 9 mm and 6 mm against Staphylococcus aureus and Escherichia coli, respectively. Nanofibers prepared with 2–3% mucilage showed uniform morphology (diameters: 12.36–26.24 μm) and significantly higher encapsulation efficiency (93.90 $$\:±\:$$ 2.1) (p < 0.05) than nanoemulsions (88.33 $$\:±\:$$ 2). FTIR analysis confirmed the successful encapsulation of Bacillus coagulans, with characteristic peaks in the ranges of 1500–1600 cm⁻¹, 2800–3000 cm⁻¹, and 3200–3500 cm⁻¹. These findings suggest that chia seed mucilage-based nanofibers offer a stable and efficient platform for probiotic delivery, with promising applications in functional foods, pharmaceuticals, and cosmetics.